Atomic-level insights in tuning defective structures for nitrogen photofixation over amorphous SmOCl nanosheets. (November 2019) - Hou, Tingting; Guo, Ruihan; Chen, Lanlan; Xie, Yangcenzi; Guo, Jiasheng; Zhang, Wenhua; Zheng, Xusheng; Zhu, Wenkun; Tan, Xiaoping; Wang, Liangbing
Abstract: Direct fixation of N2 at room temperature by photocatalysis is the most intriguing process toward sustainable production of ammonia, where chemisorption of inert N2 and delivery of photogenerated electrons to NN bond are recognized bottlenecks. Here, we develop a catalyst of amorphous SmOCl nanosheets (A-SmOCl) with remarkable activity for photocatalytic reduction of N2 . Impressively, the ammonia production rate of A-SmOCl reached 426 μmol·gcat. −1 ·h −1 under light irradiation in water without any sacrificial agents. Moreover, A-SmOCl exhibited an apparent quantum efficiency of 0.32% at 420 nm. Further mechanistic studies revealed that the existence of abundant oxygen vacancies in A-SmOCl significantly improved the adsorption and activation of N2 . Meanwhile, the enhanced Sm–O covalency promoted the delivery of photogenerated electrons to chemisorbed N2, contributing to the superior catalytic activity of A-SmOCl. Graphical abstract: A-SmOCl exhibited the ammonia production rate of 426 μmol·gcat. −1 ·h −1 attributed to the existence of abundant oxygen vacancies and enhanced Sm–O covalency.Image 1 Highlights: We developed a catalyst of amorphous SmOCl nanosheets (A-SmOCl) with abundant oxygen vacancies. The NH3 production rate of A-SmOCl reached 426 μmol·gcat. −1 ·h −1 under light irradiation without any sacrificial agents. A-SmOCl exhibited an apparent quantum efficiency of 0.32% at 420 nm. The existence of abundant oxygen vacancies in A-SmOCl significantly improved the adsorption and activation of N2 . The enhanced Sm–O covalency promoted the delivery of photogenerated electrons to chemisorbed N2 .